Pengaruh Tata Kelola, Manajemen Risiko dan Kepatuhan terhadap Nilai Perusahaan dengan Modal Intelektual sebagai Variabel Moderasi (Studi pada Perbankan yang Terdaftar di BEI Tahun 2016-2020) - Muhammad Nurdin; Rina Melsyawati; Hotman Tohir Pohan (Jurnal Riset Perbankan Manajemen dan Akuntansi, 2023)
This study aims to determine corporate governance, risk management and compliance with corporate values with the intellectual capital as a moderating model. This study uses a comparative causal method. The unit of analysis for this research uses conventional banks on the IDX in 2016-2020. The results of the study explain that governance, corporate risk management and compliance have a significant effect on firm value. then intellectual capital strengthens the significant influence of governance, corporate risk management and compliance has a significant effect on firm value. Therefore, it can be concluded that intellectual capital strengthens the significant influence of governance, corporate risk management and compliance with corporate value in conventional banks on the IDX in 2016-2020. The limitations of the research include determining research data, namely in 2016-2020 there are banks which initially only expanded conventional units to syari’a units, so that it could affect the amount of data used. The research implications include; for practical benefits (companies), namely banks that can evaluate banking risks, so that they can be considered by banks in making decisions that can affect the health of banks. For (government) policies, the results of this study can be used as material to consider various policies taken by the government or an institution in implementing the GRC, monitoring and evaluating actions taken by banks in their operational agenda. Then for investor the results of this study will be considered by investors or potential investors, especially in the investment process in banking issuers.